2019
DOI: 10.1109/tit.2019.2928301
|View full text |Cite
|
Sign up to set email alerts
|

On the Minimax Misclassification Ratio of Hypergraph Community Detection

Abstract: In this paper, community detection in hypergraphs is explored. Under a generative hypergraph model called "d-wise hypergraph stochastic block model" (d-hSBM) which naturally extends the Stochastic Block Model (SBM) from graphs to d-uniform hypergraphs, the asymptotic minimax mismatch ratio (the risk function in the community detection problem) is characterized. For proving the achievability, we propose a two-step polynomial time algorithm that provably achieves the fundamental limit. The first step of the algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
(53 reference statements)
1
28
0
Order By: Relevance
“…1) Nodes are partitioned into k ≥ 2 non-overlapping communities, in which each node is assigned to one of these k communities with probabilities {p i } k i=1 . This generalizes the setting in [30], [34] in which k = 2 and p 1 = p 2 , and the setting in [31], [40]- [42] wherein the k communities are of equal or approximately equal sizes (i.e., p i ≈ p j for all…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…1) Nodes are partitioned into k ≥ 2 non-overlapping communities, in which each node is assigned to one of these k communities with probabilities {p i } k i=1 . This generalizes the setting in [30], [34] in which k = 2 and p 1 = p 2 , and the setting in [31], [40]- [42] wherein the k communities are of equal or approximately equal sizes (i.e., p i ≈ p j for all…”
Section: Introductionmentioning
confidence: 52%
“…In particular, Ghoshdastidar and Dukkipati [26] first proposed a random hypergraph model called the d-uniform hypergraph stochastic block model (d-HSBM), in which each subset of nodes with cardinality d is generated independently as an order-d hyperedge with a certain probability that depends on the communities that the d nodes belong to. Subsequent researchers further investigated the recovery limits of d-HSBMs by developing various hypergraph clustering algorithms (such as spectral clustering methods [27]- [33], semidefinite programming-based methods [34]- [36], tensor decomposition-based methods [37], approximate-message passing algorithms [38], [39], etc) with theoretical guarantees, and characterizing the minimax misclassification ratio [40]- [42] as well as the exact recovery criterion for the special case of two symmetric communities [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning on hypergraphs has attracted significant attention due to its ability to capture higher-order structural information [58,59]. In the statistical learning and information theory literature, researchers have studied community detection problem for hypergraph stochastic block models [60,61,62]. In the machine learning community, methods that mitigate drawbacks of CE have been reported in [6,14,12,63].…”
Section: Related Workmentioning
confidence: 99%
“…Subsequently, they extended their results to sparse, nonuniform hypergraphs [19–21]. For exact recovery, it was shown that the phase transition occurs in the regime of logarithmic average degrees in [11, 12, 29] and the exact threshold was given in [27], by a generalization of the techniques in [2]. Almost exact recovery for HSBMs was studied in [11, 12, 21].…”
Section: Introductionmentioning
confidence: 99%